Who is Entitled to the Right to Respect for Family Life Under the European Union Law? - Danėlienė, Ingrida (Teisė, 2019)
[full article, abstract in English; abstract in Lithuanian] The article investigates the right to respect for family life, established by Article 7 of the Charter of Fundamental Rights of the European Union, as applied and interpreted in conjunction with the right to marry and the right to found a family, laid down in Article 9 of the Charter. The standard of protection set by European Union law regarding these rights is identified by taking into account the standard of protection of the relevant rights established by the European Convention on Human Rights and the established case law of the European Court of Human Rights. Topical issues relating to the consolidation of these individual rights at the national level in the Republic of Lithuania are also addressed in the article. In doing so, an emphasis is laid on the content of the concepts of “family” and “family life” under supranational and national law.